UPLC-MS/MS Method for Simultaneous Determination of Three Major Metabolites of Mequindox in Holothurian - Huihui Liu; Chuanbo Ren; Dianfeng Han; Hui Huang; Rongjie Zou; Huawei Zhang; Yingjiang Xu; Xianghong Gong; Xiuzhen Zhang; Yanshen Li (Journal of Analytical Methods in Chemistry)
This study developed an ultraperformance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method for the detection of three major metabolites of mequindox, including 3-methyl-quinoxaline-2-carboxylic acid, 1-desoxymequindox, and 1,4-bisdesoxymequindox (MQCA, 1-DMEQ, and BDMEQ), in holothurian. Target analytes were simplified with ultrasound-assisted acidolysis extracted without complicated enzymolysis steps. After that, each sample was centrifuged and purified by an Oasis MAX cartridge. Then, the processed samples were separated and monitored by UPLC-MS/MS. This developed method has been validated according to FDA criteria. At fortified levels of 2, 10, and 20 μg/kg, recoveries ranged from 82.5% to 93.5% with the intraday RSD less than 7.27% and interday RSD less than 11.8%. The limit of detection (LOD) of all the three metabolites ranged from 0.21 to 0.48 μg/kg, while the limit of quantification (LOQ) ranged from 0.79 to 1.59 μg/kg. On application to commercial samples, 14 of 20 samples were detected positive for the three target analytes, with positive rate at 70 percentage. The result indicated that this method was specific, sensitive, and suitable for the quantification and conformation of the three major metabolites of MEQ in holothurian.